Detecting informal green, blue, and street physical activity spaces in the city using geotagged sports-related Twitter tweets - van der Lijn, Charlotte; Ehnström, Emil; Koivisto, Sonja; Muukkonen, Petteri (Frontiers in Sociology, 2023)
Finland's natural physical environment and climate support a wide variety of informal outdoor sports, thereby motivating the population to do physical exercise in scenic environments. The vast majority of Finns enjoy outdoor recreational activities, and could thus be encouraged to post accounts of their year-round activities on social media. The focus of our analysis is on geotagged Twitter tweets, our aim being to find out in what kind of areas and spaces, spatially, users are tweeting about sporting activities. Finland has begun to shift the focus in its national sporting policies from elite athletics to providing opportunities for all that are more accessible to the general population, and thereby to improve the overall well-being of the nation. A shortcoming in these policies is that spaces for informal physical activity are not explicitly mentioned. We use the term informal with reference both to the space and to the sporting activity, whereby public spaces are used for physical activity. The case study was conducted in the Helsinki Metropolitan Area, with an emphasis on cross-country skiing as a sports activity. In a secondary analysis we concentrated on the sports people were practicing in these locations when there was no snow. The location spaces are split in to three land cover types: green, blue, and street spaces. We found that approximately half of the skiing-related tweets were geotagged in green spaces, and half in street spaces. This finding related to street space was attributable to a spatial scale error: when we checked the results manually we noticed that they referenced the sporting location in the green space. Hence, then over 90 percent of the non-ski-related tweets were geotagged in a street space. We conclude that Twitter is a beneficial tool for detecting spaces used for informal physical activity. This knowledge will help city planners and sports planners to improve informal sports facilities, which in turn will promote healthy exercise in cities.